2008
DOI: 10.3389/neuro.04.005.2007
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde tracing with recombinant rabies virus reveals correlations between projection targets and dendritic architecture in layer 5 of mouse barrel cortex

Abstract: A recombinant rabies virus was used as a retrograde tracer to allow complete fi lling of the axonal and dendritic arbors of identifi ed projection neurons in layer 5 of mouse primary somatosensory cortex (S1) in vivo. Previous studies have distinguished three types of layer 5 pyramids in S1: tall-tufted, tall-simple, and short. Layer 5 pyramidal neurons were retrogradely labeled from several known targets: contralateral S1, superior colliculus, and thalamus. The complete dendritic arbors of labeled cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 51 publications
6
86
0
1
Order By: Relevance
“…Normally, the apical dendrites of pyramidal neurons are relatively symmetric (Larsen and Callaway, 2006;Larsen et al, 2007). Previous work from our laboratory examining Golgi-Cox-stained tissue (Brown et al, 2008) or single time-point imaging of dendrites after stroke (Brown et al, 2007) has shown that peri-infarct neurons become highly asymmetric with their arbors preferentially oriented away from the site of infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, the apical dendrites of pyramidal neurons are relatively symmetric (Larsen and Callaway, 2006;Larsen et al, 2007). Previous work from our laboratory examining Golgi-Cox-stained tissue (Brown et al, 2008) or single time-point imaging of dendrites after stroke (Brown et al, 2007) has shown that peri-infarct neurons become highly asymmetric with their arbors preferentially oriented away from the site of infarction.…”
Section: Discussionmentioning
confidence: 99%
“…This expression pattern raises the possibility that there may be something unique about this population of fluorescently labeled pyramidal cells. From an anatomic perspective, GFP-or yellow fluorescent protein (YFP)-labeled cortical neurons (under the Thy-1 promoter) have a dendritic morphology and spine structure (e.g., spine length and density; (Enright et al, 2007;Holtmaat et al, 2009)) that is comparable with cortical pyramidal neurons identified with Golgi-Cox, biocytin staining, or viral transfection (Brown et al, 2008;Larsen and Callaway, 2006;Larsen et al, 2007;Nimchinsky et al, 2001). Similarly, mapping of local circuits with laser scanning photostimulation has shown that GFP-positive cortical neurons in layer 5 receive synaptic inputs that are indistinguishable from non-GFP-positive cortical neurons (Holtmaat et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…By using artificial whisking in anesthetized rats, it was suggested that the POm (i.e., paralemniscal) pathway may carry information on whisker motion, whereas the VPM (i.e., lemniscal) pathway may encode whisker touch (in addition to whisker motion). Thus, cell type-and state-specific spiking in L5 during active somatosensation (28, 29) could be mediated by these two functionally and anatomically segregated thalamocortical pathways (23).Finally, functional and morphological studies of slender-and thick-tufted neurons indicate that these output neurons also contribute to intracortical circuits (17,(30)(31)(32)(33). Here, we reconstructed the entire 3D axon projections in the vibrissal area of individual, in vivo filled slender-and thick-tufted neurons in rat vibrissal cortex by using a semiautomated tracing technique (34).…”
mentioning
confidence: 99%
“…Finally, functional and morphological studies of slender-and thick-tufted neurons indicate that these output neurons also contribute to intracortical circuits (17,(30)(31)(32)(33). Here, we reconstructed the entire 3D axon projections in the vibrissal area of individual, in vivo filled slender-and thick-tufted neurons in rat vibrissal cortex by using a semiautomated tracing technique (34).…”
mentioning
confidence: 99%
“…Retrograde viruses have been more difficult to create. The first solution to this problem was to use viruses known to cause disease through retrograde transport, such as rabies and herpes simplex virus [57][58][59][60]. Although these viruses can be modified to prevent transmission to the experimenter, they can be difficult to produce and can cause inflammation and injury to nervous tissue.…”
Section: Spatial Controlmentioning
confidence: 99%